Effect of training in self-regulation for learning mathematics (2017)
This document evidences the need of incorporating a pedagogical strategy in a B-learning environment which works as a framework for the development of the self-regulation capacity in accordance with the academic performance of mathematics. The interest of creating approach to this problem is to observe the effect of training students with the self-regulation system which is incorporated in a B-learning environment. To achieve this, the interaction among pedagogical environment (independent variable), academic performance, and self-regulation were explored. 56 students participated, men and women of the first semester who were attending a basic mathematics improvement workshop. The data were developed based on an ANCOVA analysis. The results showed consistently that self-regulation training benefits students’ learning, and as a consequence academic performance improves